Delivery Methods for RNAi in Mosquito Larvae. Issue 4 (29th July 2020) - Munawar, Kashif; Alahmed, Azzam M; Khalil, Sayed M S
Abstract: Mosquito-transmitted diseases pose a threat for a great portion of the world population. Chemical insecticides are the main tool for mosquito control. Heavy dependence on chemicals created several problems such as resistance development in many mosquito species, environmental effects, and human health issues. Other tools for mosquito control were developed and used in some parts of the world. Ribonucleic acid interference (RNAi) is a reverse genetic mechanism that was recently introduced as a new tool for pest control. Regarding mosquito, RNAi was used to study gene function and to discover genes that can be used as targets for control purposes. Several delivery methods are used to induce RNAi in mosquito larvae. Some methods such as injection and soaking are used routinely in RNAi research but have no application in the field. Other methods such as nanoparticles and microbes have some characteristics that make them good candidates for field application. In this report, we will focus on delivery methods for RNAi in mosquito larvae and will give examples for each method.